Deuterium retention and transport in ion-irradiated tungsten exposed to deuterium atoms: Role of grain boundaries - S. Markelj; J. Zavašnik; A. Šestan; T. Schwarz-Selinger; M. Kelemen; E. Punzón-Quijorna; G. Alberti; M. Passoni; D. Dellasega (Nuclear Materials and Energy, 2024)
The influence of grain boundaries on deuterium (D) retention and transport was investigated in nanocrystalline tungsten (W) by exposing the samples to sub eV D atoms. Thin tungsten films with nanometer-sized grains were produced by pulsed laser deposition on tungsten substrates. Their grain size was increased up to one micrometer by thermal annealing in vacuum up to 1223 K. Irradiation damage was created by 20 MeV W ions at 290 K. The transmission electron microscopy analysis showed one order of magnitude larger dislocation density in nanometer-grained samples compared with the larger-grained samples. The samples were after W irradiation exposed to 0.3 eV D atoms at 600 K. D retention and D depth profiles were measured by nuclear reaction analysis. In the as-deposited nanometer-grained samples, D populated the damaged region more than three times faster than in the samples with larger grains, indicating that grain-boundaries increase D transport through the material. The concentration of defects was assessed by the final D concentration in the samples. The sample with the smallest grain size showed slightly larger D concentration in the irradiated area, but the difference in the D concentration was not substantial between different-grained samples. A large D concentration in the non-irradiated nanometer-grained sample was measured which is an indication for a high defect density in the initial material. From our observations, it can be postulated that the nanocrystalline microstructure did not substantially influence the generation of irradiation-induced defects by defect annihilation at grain boundaries.